Low-Complexity Decision Feedback Equalization for Single-Carrier Massive MIMO Systems - Zhang, Xiaohui; Xing, Ling; Wu, Honghai; Ji, Baofeng; Zhang, Gaoyuan (IEEE transactions on vehicular technology, 2024)
Decision feedback equalization (DFE) has demonstrated its potential to achieve near-optimal performance in signal detection within single-carrier massive MIMO systems. However, matrix-inversion-based DFE schemes are not suitable for massive MIMO systems due to their prohibitively high computational complexity. In this paper, we investigate frequency domain DFE for signal detection in single-carrier massive MIMO systems with the goal of reducing computational complexity for practical applications. We propose a low-complexity implicit DFE scheme for single-carrier massive MIMO systems, which mitigates inter-stream and inter-symbol interference by leveraging the Neumann series (NS) expansion for matrix inversion approximation (MIA). The proposed scheme performs DFE implicitly by recursively computing forward/feedback signals using the NS expansion, thereby avoiding computationally intensive matrix inversions and forward/feedback filters calculation. Simulation and analysis results indicate that, compared to matrix-inversion-based DFE schemes, the proposed implicit DFE scheme can significantly reduce computational complexity while achieving similar performance in single-carrier massive MIMO systems. Moreover, it outperforms existing low-complexity detection methods under stringent channel conditions while maintaining similar or even lower complexity.